Effectiveness Test of Juwet Leaf Extract and Juwet Cortex Against Desreasing Blood Glucose Levels of Hiperglemic Mice: Uji Efektivitas Ekstrak Daun Juwet dan Ekstrak Kulit Batang Juwet (Syzygium cumini L.) Terhadap Penurunan Kadar Glukosa Darah Mencit (Mus musculus) yang Hiperglikemia - Ajiningrum, Purity Sabila; Amilah, Susie; Kurela, Wela Anies (Journal of Pharmacy and Science, 2021)
Diabetes melitus drugs are currently quite expensive, so they require a cheaper and more effective substitute for drugs to control glucose levels in people with diabetes melitus. Exploring local potentials using medicinal plants can be an alternative to chemical drugs. One of the medicinal plants that is thought to be used for people with diabetes mellitus is juwet. Juwet leaves are suspected to have hypoglycemic activity, because they contain flavonoid and saponin compounds. Juwet bark also contains chemical compounds, namely flavonoids, saponins, and tannins. This study aims to determine the decrease in blood glucose levels in dextrose-induced mice by giving juwet leaf extract and juwet bark extract (Syzygium cumini L.). The test animals used were 36 male mice (Mus musculus) aged 2-3 months with a weight of 20-30 grams. This type of research was carried out experimentally and the design of this study used was Completely Randomized Design (CRD), which was divided into 12 treatments and 3 replications. The 12 treatments are juwet leaf extract and juwet bark with the same dose, namely the dose of 0 mg/kg BB, 150 mg/kg BB, 200 mg/kg BB, 250 mg/kg. Data from the research were analyzed statistically using One Way ANOVA and continued with the LSD test. The results showed that administration of juwet leaf extract and juwet bark extract at various doses had a significant effect on decreasing blood glucose levels of mice. The most effective dose to reduce blood glucose levels is juwet bark extract with a dose of 250 mg/kg BB.